Analysis of Fire Water Reservoir at Onshore Receiving Facility (ORF) PT XYZ - Erwin Jonathan; Mohamad Yani; Andes Ismayana (Eduvest - Journal of Universal Studies, 2025)
The increasing number of fire incidents at oil and gas facilities in recent years, along with the results of fire risk assessments at the Onshore Receiving Facility (ORF) at PT XYZ, which is still ranked as medium, necessitates efforts to reduce the risk level to low. One such effort involves evaluating and developing the fire water reservoir at the ORF facility to ensure its adequacy according to standards. This research aims to enhance operational safety and environmental protection, considering the high fire risk at gas transmission facilities. The research methods include identifying fire-fighting facilities, calculating water requirements, and evaluating the capacity of existing reservoirs. Based on the analysis, a new reservoir was designed with estimated costs, locations, and alternatives to meet the fire-fighting water needs at the ORF. The fire-fighting facility at the ORF of PT XYZ, located in a densely populated area, has a water capacity of 16 m³, but the ideal requirement is 43 m³. It is recommended to build a 30 m³ ground tank or explore other alternatives, such as panel tanks, sea water, or PLN hydrant networks, to improve readiness for major fires and protect public safety around the ORF. The level of fire risk at the ORF of PT XYZ is categorized as medium (yellow). Therefore, the solution could involve building a new reservoir or a panel tank that is more resistant to the risk of cracks or leaks due to land subsidence or shifting.